2017
DOI: 10.1016/j.bbamcr.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Mitochatting – If only we could be a fly on the cell wall

Abstract: Mitochondria, cellular metabolic hubs, perform many essential processes and are required for the production of metabolites such as ATP, iron-sulfur clusters, heme, amino acids and nucleotides. To fulfill their multiple roles, mitochondria must communicate with all other organelles to exchange small molecules, ions and lipids. Since mitochondria are largely excluded from vesicular trafficking routes, they heavily rely on membrane contact sites. Contact sites are areas of close proximity between organelles that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 160 publications
(203 reference statements)
0
18
0
Order By: Relevance
“…In our study, ultrastructural analysis confirmed that the cardiac mitochondria in POLG mice had similar cristae density and structure as WT mice at this age, suggesting that the POLG mutation might effect another key function of mitochondria. Although mitochondria are mostly considered to be responsible for the generation of ATP, they also play a key role in the biosynthesis of macromolecules, such as lipids, heme, and iron-sulfur clusters (48,49). More recent studies have reported that mitochondria also function as signaling organelles to regulate diverse cellular functions in cells (50), and it is possible that mtDNA mutations alter these additional mitochondrial functions in cells, possibly even at a lower threshold.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, ultrastructural analysis confirmed that the cardiac mitochondria in POLG mice had similar cristae density and structure as WT mice at this age, suggesting that the POLG mutation might effect another key function of mitochondria. Although mitochondria are mostly considered to be responsible for the generation of ATP, they also play a key role in the biosynthesis of macromolecules, such as lipids, heme, and iron-sulfur clusters (48,49). More recent studies have reported that mitochondria also function as signaling organelles to regulate diverse cellular functions in cells (50), and it is possible that mtDNA mutations alter these additional mitochondrial functions in cells, possibly even at a lower threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Not just the extent of cristae biogenesis but also their positioning can be regulated by exogenous signals. Organelle contact sites between mitochondria and the ER facilitate the exchange of phospholipids, protein biogenesis, calcium signalling, mitochondrial fission and mitophagy . It is likely that these physiological processes have been optimized in the course of evolution so that they are localized at specific submitochondrial regions conducive to their efficiency, such as contact sites and/or crista junctions.…”
Section: Perspectivesmentioning
confidence: 99%
“…The shared characteristics of the peroxisomal protein import machinery and the ERAD machinery, just mentioned, constitutes an example. Interestingly, the original selective force proposed in [8], managing ROS formation associated with beta-oxidation by removing (part of) it to peroxisomes, seems to have blossomed into a full scale homeostatic mechanism in which a large part of the cellular ROS load is dealt with by a shared contribution of peroxisomes and mitochondria; see [50] and references therein.…”
Section: How Do Other Recent Findings Stack Up?mentioning
confidence: 99%